RB-SR, SM-ND AND AR-AR ISOTOPIC SYSTEMATICS OF MARTIAN DUNITE CHASSIGNY - Misawa K.; Shih C.Y.; Reese Y.; Bogard D.D.; Nyquist L.E. (My University, 2006)
Isotopic analysis of the Martian meteorite Chassigny yields a Rb-Sr age of 1406 ± 14 Ma with an initial 87Sr/86Sr ratio of 0.702251 ± 0.000034, a Sm-Nd age of 1386 ± 28 Ma with an initial ε143Nd-value of + 16.9 ± 0.3 and an 39Ar-40Ar age of 1360+ 40- 20 Ma. The concordance of these ages and the Rb-Sr and Sm-Nd initial isotopic signatures suggest that Chassigny crystallized from low Rb/Sr, light rare earth element depleted source materials ~ 1390 Ma ago. The ages and ε143Nd-values of Chassigny and the nakhlites Governador Valadares and Lafayette overlap, suggesting that they could have come from very similar mantle sources. Nakhla, Northwest Africa 998 and Yamato 000593 appear to be from similar but distinct sources. Chassigny and all nakhlites so far studied have undergone similar evolution histories. That is, chassignites/nakhlites were derived from a region where volcanism lasted at least 50 Ma and crystallized from different lava flows or subsurface sills. They probably were launched from Mars by a single impact event. The trapped Martian atmospheric 40Ar/36Ar ratios in Chassigny, nakhlites and shergottite impact glass are similar and possibly indicate minimal change in this ratio over the past ≥ 600 Ma. © 2006 Elsevier B.V. All rights reserved.
Keywords: AR-AR; CRYSTALLIZATION AGE; MANTLE SOURCE; MARTIAN METEORITES; RB-SR; SM-ND